Clinical and psychosocial context of HIV perinatally infected young mothers in Harare, Zimbabwe: A longitudinal mixed-methods study. - Zivai Mupambireyi; Victoria Simms; Webster Mavhu; Concilia Mutasa; Edward Matsikire; April Ricotta; Margaret Pascoe; Tinei Shamu; Beula Senzanje; Chiara Pierotti; Angela Mushavi; Nicola Willis; et al. (PLoS ONE)
Background The lives of adolescents and young people living with HIV (LHIV) are dominated by complex psychological and social stressors. These may be more pronounced among those perinatally infected. This longitudinal mixed-methods study describes the clinical and psychosocial challenges faced by HIV perinatally infected young mothers in Harare, Zimbabwe to inform tailored support. Methods HIV perinatally infected young mothers were recruited in 2013 and followed up in 2019. In 2013, they completed a structured interview, clinical examination, psychological screening and had viral load and drug resistance testing. A subset completed in-depth interviews (n = 10). In 2019, they were re-interviewed and had viral load testing. Data were analyzed using STATA 15.0. and thematic analysis. Results Nineteen mothers aged 17-24 years were recruited in 2013. Eleven (57.9%) were successfully recontacted in 2019; 3 had died, 2 had relocated and 3 were untraceable. In 2013, all 19 mothers were taking antiretroviral therapy (median duration 8 years, range 2-11 years) and median CD4 count was 524 (IQR 272). In 2013, eight mothers (42.1%) had virological failure (≥1000 copies/ml) (3 of whom subsequently died) and 7 (36.8%) had evidence of drug resistance. In 2019, the proportion with virological failure was 2/11 (18.1%). Six of 11 (54.5%) had switched to second line therapy. In 2013, 64.3% were at risk of common mental disorder and this risk was higher at follow-up (72.7%). Qualitative data highlighted three pertinent themes: HIV status disclosure, adherence experiences and, social and emotional support. Conclusions Findings from this study underscore the significant clinical, social and psychological challenges faced by perinatally infected young mothers. The high rates of virological failure, drug resistant mutations, mental health issues and mortality observed in this population indicate the need for tailored and comprehensive health and support services to assist these young mothers.